Heterostructure induced dispersive shear bands in heterostructured Cu. (September 2019) - Wang, Y.F.; Huang, C.X.; He, Q.; Guo, F.J.; Wang, M.S.; Song, L.Y.; Zhu, Y.T.
Abstract: Here we report the formation of dispersive shear bands in a heterostructured Cu composed of coarse-grained (CG) and ultrafine-grained (UFG) domains. Microscale digital image correlation revealed that dense shear bands evolved in a stable manner over the whole gauge section. Our observation suggests that the limited strain hardening of UFG domains and deformation heterogeneity promoted shear banding, which is a major deformation mechanism in heterostructured materials. The dispersive shear banding helped with ductility retention. Graphical abstract: Unlabelled Image